Invasive management of atrial fibrillation. Issue 3 (September 2016) - Vlachos, K.; Letsas, K. P.; Efremidis, M.
Abstract : Abstract: Atrial fibrillation (AF), the most common sustained cardiac arrhythmia, affects 1% of the general population with increased incidence in the elderly population and is an important contributor to population morbidity and mortality. This article reviews the current invasive management of AF. Pulmonary vein isolation (PVI) is the cornerstone of current ablation techniques for the treatment of paroxysmal atrial fibrillation (AF). Despite proven PVI, a subset of patients still experience recurrent arrhythmia, mostly due to a higher prevalence of non‐PV triggers. PVI is associated with worse arrhythmia‐free survival in patients with persistent AF than those with paroxysmal AF. Accumulating data have shown that elimination of atrial fibrillation 9 (AF) sources (rotors or rotational activity, drivers, electrograms with continuous activity) should be the goal in persistent AF ablation. Pulmonary vein isolation, linear lesions, and complex fractionated atrial electrograms (CFAEs) ablation have shown limited efficacy in patients with persistent AF. A combined approach using voltage, CFAEs, and dominant frequency (DF) mapping may be helpful for the identification of AF sources and subsequent focal substrate modification. The fibrillatory activity is maintained by intramural reentry centered on fibrotic patches. Voltage mapping may assist in the identification of fibrotic areas. Stable rotors display the higher DF and possibly drive AF. Furthermore, the single rotor is usually consistent with organized AF electrograms without fractionation. It is therefore quite possible that rotors are located at relatively "healthy islands" within the patchy fibrosis. This is supported by the fact that high DF sites have been negatively correlated with the amount of fibrosis. CFAEs are located in areas adjacent to high DF. In conclusion, patchy fibrotic areas displaying the maximum DF along with high organization index and the lower fractionation index are potential targets of ablation. Prospective studies are required to validate the efficacy of substrate modification in left atrial ablation outcomes. Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/4469458/Activity.aspx